Análise da distribuição espacial e racial da Razão de Mortalidade Materna brasileira - Cláudia Aparecida Avelar Ferreira; Paulo Fernando Braga Carvalho (Confins)
The aim of this study was to analyze the spatial distribution of the maternal mortality ratio in in Brazil from 2016 to 2020, considering women aged 10 to 49 years old and the issue of racial inequality. Ecological research was carried out through secondary data in the database of the Mortality Information System and Information System on Live Births. The maternal mortality ratio in 2020 (67.9) was higher than in previous years. White women mainly had a high maternal mortality ratio, especially in the north and northeast regions, and the states of Amapá and Roraima had the worst indicators in 2016 and 2020. The data show that these regions present the worst results of the state's action in the care of primary health care.